LIMITATIONS, HIDDEN EXCEPTIONS, AND RESPONSIBILITIES FOR BETTER WORKER PROTECTION - Priscillia Putri Feliana; Ida Susanti (CV. RADJA PUBLIKA, 2025)
This paper will examine the characteristics of worker exploitation that lead to unfair/indecent working conditions, the imposition of sanctions on perpetrators of exploitation, exemptions from sanctions for specific sectors, and the forms of sanctions that can be imposed. The approach to sanctions should not only serve as a deterrent to violators but also ensure the protection of victims. This study will evaluate existing labor regulations and interpret them through a socio-economic analysis to identify their weaknesses and propose improvements, aiming to create more effective regulations for worker protection. Consequently, this research employs a socio-legal study approach. One of the key findings of this study is that imposing sanctions on exploitative employers alone is insufficient to protect workers. While such sanctions may deter violations, they do not necessarily enhance worker protection. Therefore, the enforcement of civil sanctions is also crucial to ensure that victims of exploitation receive compensation for the damages they have suffered.